-7v-1=-4(v+7)

Simple and best practice solution for -7v-1=-4(v+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7v-1=-4(v+7) equation:


Simplifying
-7v + -1 = -4(v + 7)

Reorder the terms:
-1 + -7v = -4(v + 7)

Reorder the terms:
-1 + -7v = -4(7 + v)
-1 + -7v = (7 * -4 + v * -4)
-1 + -7v = (-28 + -4v)

Solving
-1 + -7v = -28 + -4v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '4v' to each side of the equation.
-1 + -7v + 4v = -28 + -4v + 4v

Combine like terms: -7v + 4v = -3v
-1 + -3v = -28 + -4v + 4v

Combine like terms: -4v + 4v = 0
-1 + -3v = -28 + 0
-1 + -3v = -28

Add '1' to each side of the equation.
-1 + 1 + -3v = -28 + 1

Combine like terms: -1 + 1 = 0
0 + -3v = -28 + 1
-3v = -28 + 1

Combine like terms: -28 + 1 = -27
-3v = -27

Divide each side by '-3'.
v = 9

Simplifying
v = 9

See similar equations:

| 4(y+7)=-7y-27 | | 3(x-7)=y | | 5x^3-2x^2-10x+4= | | 3z+2z=25-2i | | -2w+10=6(w-9) | | 10=9x-7 | | 3x^2+4y^2-6x-32y+55=0 | | 16x^3-25x=0 | | 6x-3y+18=0 | | 6-x=-10 | | 5x+16y-12z=230 | | 2y-4x-12=0 | | 10x+24y=123 | | 9x+11=7x+1 | | x(x-3)(x-5)=0 | | -1.9=-11.78 | | 6x-6-6=2x-4+4x | | -4.2+5x=3 | | 6n+13=67 | | n^2-2n=-1 | | 2-5=4-x | | -10t+25+3t=2t-9 | | 95-5x=13x+19 | | 2-4=4-x | | 124-5x=40x+24 | | 2x(x+21)=756 | | 10x+30=10x+30 | | 6(x-2)+5=-13 | | 3a+5=7 | | -8y-13=4y+11 | | 3(2x+18)-4x-22=7x-18 | | (2x+14)(x+14)=952 |

Equations solver categories